2014
DOI: 10.1109/tro.2014.2361937
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Constraint Control of a Powered Prosthetic Leg: From Simulation to Experiments With Transfemoral Amputees

Abstract: Recent powered (or robotic) prosthetic legs independently control different joints and time periods of the gait cycle, resulting in control parameters and switching rules that can be difficult to tune by clinicians. This challenge might be addressed by a unifying control model used by recent bipedal robots, in which virtual constraints define joint patterns as functions of a monotonic variable that continuously represents the gait cycle phase. In the first application of virtual constraints to amputee locomoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
190
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 44 publications
0
190
0
Order By: Relevance
“…The test was done on the robot leg from -11.50 o to 11.50 o and obtained high control action about 30 N.m. In 2014, Gregg et al [15] implemented virtual constraints that unify the stance period, coordinate ankle and knee control, and accommodate clinically meaningful conditions on a powered prosthetic leg. The saturate prosthesis torques at 80 N.m to simulate the torque limit of the experimental prosthesis.…”
Section: Related Workmentioning
confidence: 99%
“…The test was done on the robot leg from -11.50 o to 11.50 o and obtained high control action about 30 N.m. In 2014, Gregg et al [15] implemented virtual constraints that unify the stance period, coordinate ankle and knee control, and accommodate clinically meaningful conditions on a powered prosthetic leg. The saturate prosthesis torques at 80 N.m to simulate the torque limit of the experimental prosthesis.…”
Section: Related Workmentioning
confidence: 99%
“…Rather than model all of the DoF of the foot, the function of the foot and ankle is modeled using a circular foot plus an ankle joint [23] to capture both the center of pressure movement [38] and the positive work performed at the stance ankle [39]. To account for the lack of information transmitted between the human and prosthesis, the full model can be divided into a prosthesis subsystem and a human subsystem [19]. The prosthesis subsystem consists of the prosthetic thigh, shank, and foot.…”
Section: Modelmentioning
confidence: 99%
“…Recent work has shown that human joint patterns are parameterized well by a phase variable [16], [17], which is a kinematic quantity that measures how far a step (or stride) has progressed. In addition, pre-clinical work has demonstrated that phase-based controllers can successfully control powered prostheses [18], [19], although determination of the best control strategy is still very much an open question.…”
Section: Iintroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,17 However, only modest simplification can be achieved since at least 3 states are typically defined for levelground walking, and parameter values differ across tasks (i.e., ramp ascent/descent, stair ascent/descent). 16,18,38 Another solution to tune fewer parameters is to associate parameter values with one another 36 or with other intrinsic biomechanical measures (e.g., prosthesis joint angles, prosthesis load, walking speed, foot center of pressure, effective leg shape).…”
Section: Introductionmentioning
confidence: 99%